Combination of single-cell and bulk RNA seq reveals the immune infiltration landscape and targeted therapeutic drugs in spinal cord injury - Zhang, Qing; Yu, Beibei; Zhang, Yongfeng; Tian, Yunze; Yang, Shijie; Chen, Yongfeng; Wu, Haining (Frontiers in Immunology, 2023)
Background: In secondary spinal cord injury (SCI), the immune microenvironment of the injured spinal cord plays an important role in spinal regeneration. Among the immune microenvironment components, macrophages/microglia play a dual role of pro-inflammation and anti-inflammation in the subacute stage of SCI. Therefore, discovering the immune hub genes and targeted therapeutic drugs of macrophages/microglia after SCI has crucial implications in neuroregeneration. This study aimed to identify immune hub genes and targeted therapeutic drugs for the subacute phase of SCI. Methods: Bulk RNA sequencing (bulk-RNA seq) datasets (GSE5296 and GSE47681) and single-cell RNA sequencing (scRNA-seq) dataset (GSE189070) were obtained from the Gene Expression Omnibus database. In the bulk RNA-seq, the R package ‘limma,’ ‘WGCNA,’ and ‘CIBERSORT’ were used to jointly screen key immune genes. Subsequently, the R package 'Seurat' and the R package 'celldex' were used to divide and annotate the cell clusters, respectively. After using the Autodock software to dock immune hub genes and drugs that may be combined, the effectiveness of the drug was verified using an in vivo experiment with the T9 SCI mouse model. Results: In the bulk-RNA seq, B2m, Itgb5, and Vav1 were identified as immune hub genes. Ten cell clusters were identified in scRNA-seq, and B2m and Itgb5 were mainly located in the microglia, while Vav1 was mainly located in macrophages. Molecular docking results showed that the proteins corresponding to these immune genes could accurately bind to decitabine. In decitabine-treated mice, the pro-inflammatory factor (TNF-α, IL-1β) levels were decreased while anti-inflammatory factor (IL-4, IL-10) levels were increased at 2 weeks post-SCI, and macrophages/microglia transformed from M1 to M2. At 6 weeks post-SCI, the neurological function score and electromyography of the decitabine treatment group were also improved. Conclusion: In the subacute phase of SCI, B2m, Itgb5, and Vav1 in macrophages/microglia may be key therapeutic targets to promote nerve regeneration. In addition, low-dose decitabine may promote spinal cord regeneration by regulating the polarization state of macrophages/microglia.